Pierre-André Juven, Une santé qui compte ? Coûts et tarifs dans la politique hospitalière française - Pierre-André Juven (Revue de la Régulation)
How costs and tariffs have become pivotal policy instruments to govern public hospitals in France since the early 1980’s? What kind of controversies do they produce and what feedback effect do these controversies have on these instruments? These are the questions I propose to answer in this PhD dissertation by analysing the genealogy, the uses and the transformations of several policy devices: information system, cost accounting, budgetary regulation instrument and pricing payment system. Combining a sociology of policy instruments and science and technology studies, these devices are analysed in the multiple sites where they spread: ministry of Health, public agency, research centres in management studies, hospital federations, patients organizations and public hospitals. The dissertation exposes how these devices have turned public hospitals into accounting and financial entities. I specially focus on the pricing payment system (called T2A) which is analysed as a qualculation instrument as it qualifies and quantifies patients, stays in hospitals, diseases, and public hospital itself. The dissertation shows how this qualculation process produces metrological controversies in which actors put into question the way things are qualculated.